Plasmon‐Enhanced Photodetection in Ferromagnet/Nonmagnet Spin Thermoelectric Structures. (12th August 2018) - Jeon, Chul‐Yeon; Baek, Kwang Min; Kim, Shinho; Kim, Dong‐Jun; Jang, Min Seok; Jung, Yeon Sik; Park, Byong‐Guk
Abstract: The photothermoelectric (PTE) effect that originates from the temperature difference within thermoelectric materials induced by light absorption can be used as the mechanism for a light sensor in optoelectronic applications. In this work, a PTE‐based photodetector is reported using a spin thermoelectric structure consisting of CoFeB/Pt metallic bilayers and its signal enhancement achieved by incorporating a plasmonic structure consisting of Au nanorod arrays. The thermoelectric voltage of the bilayers markedly increases by 60 ± 10% when the plasmon resonance condition of the Au nanorods is matched to the wavelength of the incident laser. Full‐wave electromagnetic simulations reveal that the signal enhancement is due to the increase in light absorption and consequential local heating. Moreover, the alignment of the Au nanorods makes the thermoelectric voltages sensitive to the polarization state of the laser, thereby enabling the detection of light polarization. These results demonstrate the feasibility of a hybrid device utilizing plasmonic and spin‐thermoelectric effects as an efficient PTE‐based photodetector. Abstract : Enhanced photodetection is demonstrated in spin thermoelectric device by combining plasmonic Au nanorod arrays. The photothermoelectric (PTE) voltage increases by ≈60% when the plasmon resonance condition of the Au nanorods is matched to the wavelength and polarization of the laser. This offers a hybrid device utilizing plasmonic and spin‐thermoelectric effects as an efficient PTE‐based photodetector.